Comfort-oriented nursing interventions to improve quality of life in hemodialysis patients: A systematic review - Abiyyu Faqih Dhiyaus Suud Ahmad; Enny Mulyatsih; Dwi Retno Sulistyaningsih (Lentera Perawat, 2026)
Background: Patients undergoing hemodialysis frequently experience fatigue, pain, muscle cramps, and reduced functional capacity, which adversely affect their quality of life. Non-pharmacological nursing interventions using a comfort-oriented approach are believed to improve patients’ physical comfort and functional status. However, the available recent evidence remains heterogeneous and has not been systematically synthesized. Objective: This study aimed to review and synthesize recent evidence regarding the effectiveness of comfort-oriented nursing interventions in improving physical comfort, functional capacity, and quality of life among patients undergoing hemodialysis. Methods: A systematic review was conducted by searching Scopus, PubMed, ScienceDirect, Google Scholar, and relevant research registries for studies published between 2020 and April 2026. Eligible studies included randomized controlled trials, quasi-experimental studies, observational studies, and qualitative studies reporting outcomes related to comfort, functional capacity, and quality of life among adult patients undergoing hemodialysis. Methodological quality was assessed using the Cochrane Risk of Bias Tool, Newcastle–Ottawa Scale, and Critical Appraisal Skills Programme checklists. Data were extracted and narratively synthesized to describe intervention effects, underlying mechanisms, and heterogeneity across the findings. Results: Of the 801 records identified, 10 studies met the inclusion criteria. The interventions demonstrated improvements in physical comfort, muscle strength, mobility, and quality of life. Multicomponent and technology-based interventions also improved patient engagement, treatment adherence, and nutritional markers. Heterogeneity in study populations, intervention duration, and study designs affected the strength of the evidence. Nevertheless, consistent patterns indicated that nurse-delivered interventions provided beneficial outcomes within dialysis care settings. Conclusion: Comfort-oriented nursing interventions appear to be safe, feasible, and effective in improving physical comfort, functional capacity, and quality of life among patients undergoing hemodialysis. The findings support the integration of physical exercise, relaxation techniques, and multicomponent strategies into routine dialysis nursing care.